2014
DOI: 10.1161/circep.113.000919
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Mechanism Underlying Hypothermia-Induced Ventricular Tachycardia/Ventricular Fibrillation in the Setting of Early Repolarization and the Protective Effect of Quinidine, Cilostazol, and Milrinone

Abstract: Background Hypothermia has been reported to induce ventricular tachycardia and fibrillation (VT/VF) in patients with early repolarization (ER) pattern. This study examines the cellular mechanisms underlying VT/VF associated with hypothermia in an experimental model of ER syndrome (ERS) and examines the effectiveness of quinidine, cilostazol and milrinone to prevent hypothermia-induced arrhythmias. Method and Results Transmembrane action potentials (AP) were simultaneously recorded from 2 epicardial and 1 end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 22 publications
3
71
0
Order By: Relevance
“…161, 168, 215, 216 Interestingly, a recent experimental study suggests that quinidine exerts a protective effect against hypothermia-induced VT/VF in a J wave syndrome model. 217 …”
Section: Approach To Therapymentioning
confidence: 99%
“…161, 168, 215, 216 Interestingly, a recent experimental study suggests that quinidine exerts a protective effect against hypothermia-induced VT/VF in a J wave syndrome model. 217 …”
Section: Approach To Therapymentioning
confidence: 99%
“…It remains unclear whether the risk of the positive chronotropic effects of cilostazol may outisoform of the enzyme, which is selectively localized in the microsomal fraction 39) . Moreover, some studies have shown that cilostazol had anti-arrhythmogenic 40,41) or therapeutic neutrality in arrythmias 42) . Additionally, cilostazol was reported to prevent episodes of VF 43) or failed to prevent them in Brugada patients 44) .…”
Section: Discussionmentioning
confidence: 99%
“…6 In the patient with hypothermia, the prominent J wave is induced as the result of a marked accentuation of epicardial AP, probably due to the effect of cold temperatures, which slow the activation kinetic of I to to less than that of the I Ca current. 6,7 Loss of the AP duration usually is heterogeneous, resulting in marked abbreviation of the AP at some sites but not others. The AP dome of cells with relatively intact morphologies propagates to adjacent, rapidly repolarized cells to produce phase 2 reentry.…”
Section: Discussionmentioning
confidence: 99%